(3NQjWI QjGV GdCWaGd aj dHfGfs - (3HThQ, fLdGA fUjQs ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2002)
(3jJSe GdJYdje aj eQMdI QjGV GdCWaGd HGddGeQcRjI MJi OGNd GdEWGQ GdQSej faSg, adjS gfGc CjI eQLYjI eQcRjI eYfjI HQjGV GdCWaGd JVY GdSjGSGJ hJMOO GdCgOGa hGdeYGjjQ hGdTQhW, hJbJQM GdJTQjYGJ GddGReI, MjK JJYOO GdCLgRI GdQSejI GdeYfjI HeQMdI GdQhVI, Ef OGNd hRGQI GdJQHjI Ch NGQLgG(B. (3dG JVY GdhRGQI TQhWkG ddQhVI Ch deYdeGJgG YOG eG oMOO ddJYdje GdGHJOGFj(B. (3YGe (B2000 (3CUHMJ eQMdI GdQhVI JTed KdGKI Uaha ddCWaGd ef YeQ (B3-6 (3SfhGJ(B. (3hJaJbQ GdJTQjYGJ GdQSejI dCjI ETGQI Edi GdCWaGd Phj GdGMJjGLGJ GdNGUI(B. (3JVe QjGV GdCWaGd (B23(3,(B9% (3ef GdCWaGd ef YeQ (B3-4 (3SfhGJ h(B61(3,(B7% (3ef GdCWaGd ef YeQ (B4-6. (3hjSJbWH GdJYdje GdNGU HTbjg GdeLGfj hZjQ GdeLGfj hZjQ GdeLGfj GdfSHI GdCYdi ef gDdGA GdJdGejP hjJQcR aj GdeOf GdQFjSjI, HjfeG jJQcR GdbWGY GdQSej aj GdefGWb GdHYjOI Yf GdYGUeI, hNGQL GdeOf GdQFjSjI(B.s
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Kindergarten; Maternelle; (3QjGV GdCWaGds